INVESTIGATING THE VIETNAMESE EFL LEARNERS’ AFFECTIVE AND COGNITIVE ATTITUDES TOWARDS THE IELTS LISTENING TEST - Tran, Thao Thi; Nguyen, Huong Thu (Advances in Social Sciences Research Journal, 2018)
The sustainable societal development generates the growing demand of Vietnamese EFL learners who would like to study abroad and one of the most popular English language proficiency test to be eligible for overseas universities is the International English Language Testing System (IELTS). Consequently, the focus of language systems has been emphasized within the context of teaching and learning English in Vietnam, particularly in foreign language centers in Vietnam. Of the four language skills, listening has been considered as the most widely used language skill which has drawn a lot of attention from many researchers due to its primary importance in second language acquisition and learning (Rubin, 1994). The time we spent on listening exceeds the time spent on speaking, reading, and writing. However, its great importance has just received recognition lately as a tool to facilitate learners’ language learning (Vandergrift & Goh, 2012). A number of studies have been conducted to examine the validity of the IELTS test along with figuring out the relationship between the IELTS practice courses and learners’ performance (Ata, 2015). Nevertheless, few empirical studies on the Vietnamese EFL learners’ attitudes towards the IELTS listening test were carried out. Therefore, this study is conducted for the purpose of filling the gap in the literature in the local context of teaching and learning the IELTS test in Vietnam. Thus, the research aims at examining the Vietnamese EFL learners’ attitudes towards the areas of the test that learners have positive affection, their perceptions of challenges of taking the IELTS listening test.